SOLUSI PRAKTIS UNTUK MUTU PENDIDIKAN ISLAM DI INDONESIA - Muslahuddin As’ad; Muzakkir Ahlisan (IQRA : JURNAL MAGISTER PENDIDIKAN ISLAM, 2022)
ABSTRACTPractical solutions for improving the quality of Islamic education in Indonesia are: First, formulating a clear vision, mission and goals of the institution, Second, building truly professional leadership, Third, preparing educators who are truly educator-minded, Fourth, perfecting student recruitment strategies Fifth, trying hard to raise awareness to students that learning is the most basic obligation that determines their future, Sixth, formulating a curriculum that is in accordance with the needs of students and society, Seventh, exploring learning strategies that can accelerate students' abilities that are still low to become competitive graduates. Eighth, explore financial sources and develop them productively. Ninth, building adequate facilities and infrastructure. Tenth, orienting learning strategies to the tradition of developing knowledge, creativity, and skills. Eleventh, strengthening the methodology in terms of learning, thinking and research. Twelfth, conditioning a safe, comfortable and stimulating learning environment. Thirteenth, conditioning an Islamic environment both in worship, work, social interaction, and cleanliness. Fourteenth, trying to improve the welfare of employees above the average welfare of employees of other educational institutions. Fifteenth, realizing a high work ethic among employees through moral contracts and work contracts. Sixteenth, trying to provide excellent service to anyone. Seventeenth, increase promotion to build image. Eighteenth, publicly publish the quality of the learning process and results to the public. Nineteenth, build a network of cooperation with other parties that are profitable. Keyword : Practical solutions, quality, Islamic education